CRIMINAL JUSTICE SYSTEM AND BANDITS’ CRIMINAL VICTIMIZATION IN NORTHWEST NIGERIA - Sabo, Sarkinnoma Yahaya; Yusuf, Usman Alhaji; Apake, Faridah Ladi (African Journal of Social and Behavioural Sciences, 2024)
The criminal justice system is tasked with enforcing obedience to the law, determining whether the laws have been broken, imposing punishment on lawbreakers, and ensuring that justice is done, among others. The CJS is, therefore, saddled with the responsibility of identifying, arresting, prosecuting, and penalizing offenders. To ascertain whether the CJS is effective in performing its functions or otherwise, the extent to which the system forestalls criminal victimization and sanctions lawbreakers is taken into consideration. The objective of this paper is to assess the effectiveness of the CJS in handling the menace of armed banditry in the northwest region. The paper is premised on routine activity theory and based on secondary sources of data such as reports, journal articles, institutional and organizational publications, and textbooks. Data were obtained from online sources and examined critically. The paper submits that the criminal justice system is failing to tackle armed banditry on the grounds that, despite the large number of bandits terrorizing the region, only a few of them have been arrested. The few that have been arrested are hardly convicted and punished for their crimes. It concludes that the failure of the CJS to tackle armed banditry would embolden the bandits and result in the further escalation of the menace. Among other things, the paper recommends intensification of policing in the region to identify and apprehend offenders, and arrested bandits should be convicted and punished without any delay to serve as a deterrent to others.